Kebumen Adhi Tagguh Mandiri (KATAM) Program Pengabdian Kepada Masyarakat Kewirausahaan Desa Berbasis Digital - Evi Rosalina Widyayanti; Suci Utami Wikaningtya; Ary Sutrischastini; Lilik Ambarwati; Anggie Febriyanti (JCSE: Journal of Community Service and Empowerment, 2025)
The community of Grujugan Village, Petanahan District, Kebumen Regency, has a high interest in Entrepreneurship. However, this village faces various problems in aspects of Entrepreneurship, in general, and Digital Entrepreneurship, in particular. Therefore, Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha partnered with Grujugan Village to organize the KATAM Program, with the theme "Building Digital Entrepreneurship." There were 25 participants, selected using purposive sampling based on their interest in becoming digital entrepreneurs. The training method used was a focus group discussion, divided into 5 groups, with the focus on discussing village potential mapping, challenges, and suggestions. Then, eight training sessions were conducted and evaluated through pre-tests and post-tests, with the training results showing satisfactory outcomes: an average pre-test score of 64 and an average post-test score of 86. Subsequently, interest groups were formed, resulting in 6 interest groups, and participants committed to the success of the KATAM program through an integrity pact.